PERAN EDUKASI DAN EVALUASI INDEKS MASSA TUBUH SERTA RASIO PINGGANG-PINGGUL SEBAGAI UPAYA DETEKSI DINI RISIKO SINDROM METABOLIK DI CENGKARENG - Sari, Triyana; Santoso, Alexander Halim; Destra, Edwin; Jap, Ayleen Nathalie; Teguh, Stanislas Kotska Marvel Mayello (BAMALA Institute, 2025)
Metabolic syndrome is characterized by a cluster of metabolic abnormalities associated with body fat distribution, particularly the accumulation of visceral fat. Body mass index (BMI) and waist-to-hip ratio (WHR) are simple yet effective anthropometric parameters that can serve as indicators of metabolic risk. In this study, anthropometric assessments were conducted on 57 participants at the Cengkareng Baptist Foundation School. Measurements included BMI, waist circumference, and hip circumference, which were used to calculate WHR. The data were analyzed descriptively to evaluate body fat status and distribution. The mean BMI was 26.54, while the mean WHR was 0.89. A total of 59.65% of participants fell into the obesity category, and 68.42% exhibited central obesity based on WHR values. These elevated BMI and WHR readings reflect excessive fat accumulation and a higher tendency for metabolic risk. Excessive caloric intake is likely a contributing factor to this disproportionate fat distribution. BMI and WHR assessments can be utilized as practical screening tools for the early identification of metabolic syndrome risk in the adult population. Keywords: Metabolic Syndrome, Body Mass Index, Waist-To-Hip Ratio, Central Obesity, Anthropometry